Class XI Students' Science Literacy Ability Profile on Biology Material In MAN 1 KOLAKA - Khairul Mahdi (RADINKA JAYA UTAMA PUBLISHER, 2024)
Scientific literacy is defined by PISA as the ability to use scientific knowledge, identify questions, and draw conclusions based on evidence, to understand and make decisions regarding nature and changes made to nature through human activities. Scientific literacy is very important because, first, understanding. This research is exposure-facto research. This research aims to determine the scientific literacy abilities of class XI MIPA MAN 1 KOLAKA students in biology material. The research method used is a qualitative descriptive method. The research subjects consisted of 33 students from class XI MIPA 1 and XI MIPA 2. The research instrument used was a written test in the form of multiple-choice via Google Forms. Results of the scientific literacy abilities of the (Gusmaweti et al., 2022) class. The research results showed that students' scientific literacy abilities were classified as low, with an average percentage score of 47% for Class XI MIPA 1 and 70% for Class XI MIPA 2.